The effects of gratifications, flow and satisfaction on the usage of livestreaming services - Hsu, Chin Lung; Lin, Judy Chuan-Chuan (Library hi tech, 2023)
PurposeThis study combines uses and gratifications theory and flow theory to create an integrated model that predicts continuance intention to use and satisfaction with livestreaming services.Design/methodology/approachThe proposed model was empirically evaluated using survey data collected from 304 users about their perceptions of livestream services.FindingsThe results indicate that gratifications such as entertainment, informativeness and sociability were all positively related to satisfaction. The authors find that flow mediates the impact of interactivity and telepresence on satisfaction. Notably, sociability gratification and satisfaction had a significant impact on a user's intention to continue to use livestreaming services and accounted for 77% of the variance.Originality/valueThe study adds to the body of knowledge by demonstrating the uses and gratifications theory and flow theory in live stream services. In addition, the findings may provide useful insights for live stream services streamers and marketers.